Analysis of the hemotherapy support in an oncology hospital considering the COVID-19 pandemic - Magalhães, Nathalia Noyma Sampaio; Lopes, Jordana Alícia Silveira; Rodrigues, Andressa de Araújo, Neto; Gusmão, Amanda do Carmo; Rodrigues, Luisa de Oliveira Werneck; Rodrigues, Daniela de Oliveira Werneck; Vieira, Roberta Wolp Diniz; Cintra, Jane Rocha Duarte (Brazilian Journal of Oncology, 2022)
Objectives: The purpose of this study was to analyze the impact of COVID-19 on the use of blood components in an oncology hospital.Material and Methods: Retrospective cross-sectional quantitative nature cohort, with comparative analysis of blood component requests by an oncology hospital in the city of Juiz de Fora, Minas Gerais, Brazil, in 2019 and 2020.Results: There was a reduction of 14.36% in the requests for blood components at the oncology service in 2020 (p-value = 0,002), with a reduction of 27.33% for platelet concentrate (p-value = 0,006). The rate of attendance of Hemominas to requests for blood components at the oncology hospital was 97.99% in 2019 and 94.36% in 2020.Conclusion: The pandemic affected blood collection and supply due to the decrease in blood donors' attendance. The suspension of elective surgeries and the rational prescription of blood components allowed the rate of attendance maintenance by the blood bank. In this scenario, it is important to monitor the supply and demand for blood components in hospitals and apply strategies that optimize their use.
Keywords: Blood transfusion; SARS-CoV-2; Oncology service, Hospital; Hemotherapy service; Surgical oncology